Optimasi Pengendalian Persediaan Bahan Baku Kelapa Sawit dengan menggunakan Metode Period Order Quantity (POQ) : Studi Kasus: Pmks PT. Gruti Lestari Pratama (Lembag, 2026)
This research aims to control the planning of inventory control of palm raw materials to obtain the optimal quantity of raw material orders at PT. Gruti Lestari Pratama in 2020. The method used in this research is the model of Period Order Quantity (POQ) method which is the development of the Economic Order Quantity (EOQ) method. The result of this research obtained an optimal order quantity using the POQ method in 2020 which is 7.563,08 tons. The frequency of ordering based on company policy is 314 times in a year, while using the POQ method the order frequency 23 times in a year. Where safety stock with POQ method of 2.702,50 tons and reorder point of 3.256,35 tons. Total inventory cost of palm raw material by using POQ method of Rp. 8.907.361.822 in a year. Overall, this study shows that the application of the POQ method in controlling palm oil raw material inventory at PT. Gruti Lestari Pratama provides optimal results in reducing order frequency, saving costs, and ensuring timely raw material availability. The results of this study can serve as a basis for the company to implement a more efficient and effective inventory control system, supporting smooth production at a more affordable cost.